Developing and optimizing microfluidics platform for fabricating lignin nanoparticles. - Yadav, Deependra (My University, 2021)
Introduction: Lignin is a complex organic polymer, produced in large quantities as a by-product from pulp and paper industries. Despite of large-scale production, lignin is not being utilized for high value applications. Recently, researchers are showing greater interest in fabricating lignin-based nanoparticles for drug delivery and other application. However, it is challenging to fabricate lignin nanoparticles due to its complex chemical structure. Microfluidics technology used for nanoparticle synthesis because it works on microscale dimension with rapid and tunable mixing for better control over nanoprecipitation by controlling different parameters like flow rate, precursor and mixing time. The objective of this study is to develop method to fabricate lignin nanoparticles using microfluidics platform. Material and methods: Two type of microfluidics chips were used for sequential precipitation, one consisting of two tapered ends and another with one tapered end. Kraft lignin (0.1%) was dissolved in ethylene glycol and lignin was precipitated with acetone and NaOH (0.1M). The fabricated nanoparticles were characterised by dynamic light scattering (DLS) and transmission electron microscope (TEM). Result and Discussion: Two tapered end microfluidics chip were used to precipitate lignin because two solvent, acetone as counter solvent and NaOH as triggering precipitation was utilized, resulting nanoparticles of hydrodynamic particle size 162.5±1.82 nm, PDI 0.12±0.02 and zeta potential -24.6±2.17 mV at FRR 2:20:1 ml/hr (lignin:2ml/hr, acetone:20ml/hr, and NaOH:1ml/hr) were obtained. Whereas hybrid lignin nanoparticles (Ultra-small nanoparticles trapped in the lignin matrix) with hydrodynamic particle size of 129.73±5.91 nm, PDI 0.19±0.003 and zeta potential -15.5 mV were fabricated by sequentially precipitating kraft lignin with dual microfluidics chips setup (two tapered end and one tapered end chip). The solution from two tapered end chip was directly transferred at the rate of 23 ml/hr to the inner inlet of one tapered end chip, and precipitated at the FRR 3:20 ml/hr (3ml/hr:NaOH 0.1M) and 20ml/hr:acetone) as respective solution were infused in the outer most channel of one tapered end chip. Particles characterized with TEM showed hybrid nanoparticles consist of Ultra small primary particles were embedded in lignin matrix. Conclusion: TEM image analysis suggest that we successfully developed method to fabricate hybrid lignin nanoparticles with the average size range from 20-50 nm utilizing microfluidics platform. Morphological analysis by TEM shows that nanoparticles are composed of ultra-small primary nanoparticles of 2-4 nm were trapped in matrix of different material. Further chemical characterization of this nanoparticles will help to understand its application.
Keywords: lignin, nanoparticles, nanoprecipitation, microfluidics